(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and laboratory characteristics of preeclampsia in pregnant women with underlying medical conditions. Methods: A cross-sectional descriptive study was conducted on 205 eligible participants at National Hospital of Obstetrics and Gynecology from January 2023 to December 2025. Results: The mean maternal age was 33.86 ± 5.86 years. Severe preeclampsia accounted for the majority of cases (80.98%). Statistically significant differences were observed between the severe preeclampsia group and the non-severe group regarding urea, AST, ALT, LDH, MHVC, and fetal birth weight. Hypertension was the most common underlying comorbidity and was significantly associated with preeclampsia (OR = 3.12; p < 0.05). Conclusion: Severe preeclampsia accounted for a high proportion of cases. Hypertension was the most common chronic comorbidity and may contribute to the increased risk and severity of preeclampsia, along with other underlying medical conditions.